Effect of Changes Turbidity on Oxygen Solubility in Fish Pond Water Electrocoagulation Process - Sutanto, Sutanto; Supriyanto, Toto; Widjajanto, Danang (Department of Chemical Engineering, Politeknik Negeri Bandung, 2023)
The water used for fish farming by the Mina Lestari is very dirty, because many soil particles are dissolved in water. The water with high dirty in generally has very high turbidity. So that oxygen is difficult to dissolve in water and is not sufficient for fish life. So many fish die, due to insufficient oxygen for breathing. To reduce water turbidity is treated by electrocoagulation process combined with the aeration process. The aim of the research was to study the effect of changes in turbidity on dissolved oxygen in water. The study began by measuring the turbidity using a turbidimeter and dissolved oxygen using a DO meter. Furthermore, pour 10 liters of water into the electrocoagulation process tank. The electrocoagulation was carried out at 12 volt or 0,3 ampere for 10 minutes. The process was stopped, then the water flowed into the settling tank and left for 30 minutes to precipitate of the dirt. The water flowed into a holding tank and followed aeration process by flowing air at a rate of 500 cc per minute for 30 minutes. Then followed measuring turbidity by turbidimeter and dissolved oxygen by DO meter. Subsequent studies were carried out using the same procedure with an interval of 10 minutes processing time for electrocoagulation process. The results showed that an increase in processing time can reduce water turbidity from 68 NTU to 45 NTU or 33.82% and increase dissolved oxygen from 2.8 mg/L to 5.3 mg/L or 89.29% at 50 minutes processing.